2006
DOI: 10.1117/1.2209215
|View full text |Cite
|
Sign up to set email alerts
|

Balancing detector effects with aberrations in the design of wide-field grazing incidence x-ray telescopes

Abstract: Most imaging systems today include a mosaic detector array in the focal plane. Optical designers of astronomical telescopes typically produce a design that yields a superb on-axis aerial image in the focal plane, and detector effects are included only in the analysis of the final system performance. Aplanatic optical designs ͑corrected for spherical aberration and coma͒ are widely considered to be superior to nonaplanatic designs. However, there is little merit in an aplanatic design for wide-field application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…When surface scatter effects and detector effects are included in a complete systems engineering analysis of image quality for such systems, there is often even less merit to an optical design that satisfies the Abbe sine condition. [10][11] Our complete systems engineering analysis of image quality indicated that our optimum non-aplanatic HH SXI design would result in an 80% increase in the number of spatial resolution elements in the solar disc over what could be achieved by the classical Wolter Type I baseline design. Figure 5 is an on-orbit image recorded with the GOES-13 SXI instrument utilizing a non-aplanatic HH grazing incidence X-ray telescope design optimized for an 18 arc min OFOV.…”
Section: The Solar X-ray Imager (Sxi)mentioning
confidence: 97%
“…When surface scatter effects and detector effects are included in a complete systems engineering analysis of image quality for such systems, there is often even less merit to an optical design that satisfies the Abbe sine condition. [10][11] Our complete systems engineering analysis of image quality indicated that our optimum non-aplanatic HH SXI design would result in an 80% increase in the number of spatial resolution elements in the solar disc over what could be achieved by the classical Wolter Type I baseline design. Figure 5 is an on-orbit image recorded with the GOES-13 SXI instrument utilizing a non-aplanatic HH grazing incidence X-ray telescope design optimized for an 18 arc min OFOV.…”
Section: The Solar X-ray Imager (Sxi)mentioning
confidence: 97%
“…A detailed analysis of detector effects was also included [52]. Figure 11 shows the comparison of the image quality predictions and experimental on-orbit data taken shortly after launch [51].…”
Section: Systems Engineering Analysis Of Image Qualitymentioning
confidence: 99%